Practical Guilt : Moral Dilemmas, Emotions, and Social Norms. - Greenspan, P. S. (Oxford University Press, 1995)
P.S. Greenspan uses the treatment of moral dilemmas as the basis for an alternative view of the structure of ethics and its relation to human psychology. Greenspan argues that dilemmas may be regarded as possible consequences of a set of social rules designed to be simple enough to beteachable. Where these rules prohibit action either way, the problematic motivational force of dilemmas can be explained by reference to the role of emotion as a substitute for action. Guilt is seen as a natural but contested candidate for the sort of emotional sanction for wrongdoing that mightsupply motivational.